Segmentation, revenue management and pricing analytics - Bodea, Tudor; Ferguson, Mark, 1969- (New York, N.Y. : Routledge, 2013)
"The practices of revenue management and pricing analytics have transformed the transportation and hospitality industries, and are increasingly important in industries as diverse as retail, telecommunications, banking, health care and manufacturing. Segmentation, Revenue Management and Pricing Analytics guides students and professionals on how to identify and exploit revenue management and pricing opportunities in different business contexts. Bodea and Ferguson introduce concepts and quantitative methods for improving profit through capacity allocation and pricing. Whereas most marketing textbooks cover more traditional, qualitative methods for determining customer segments and prices, this book uses historical sales data with mathematical optimization to make those decisions. With hands-on practice and a fundamental understanding of some of the most common analytical models, readers will be able to make smarter business decisions and higher profits"--
ch. 1. The ideas behind customer segmentation -- ch. 2. Forecasting -- ch. 3. Promotion forecasting -- ch. 4. Capacity-based revenue management -- ch. 5. Unconstraining -- ch. 6. Pricing analytics -- ch. 7. Dynamic and Markdown pricing -- ch. 8. Pricing in business-to-business environments -- ch. 9. Customer behavior aspects of pricing.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Revenue management; Pricing; Market segmentation; Electronic books